A single centre case series of gallstone sigmoid ileus management. (2017) - Farkas, Nicholas; Karthigan, Ravindran; Lewis, Trystan; Read, James; Farhat, Sami; Zaidi, Ahsan; West, Nicholas
Highlights: Gallstone sigmoid ileus is a rare condition caused by a stone obstructing the sigmoid colon. Manual evacuation of an obstructing gallstone has not previously been documented before. No center has reported more than one case; consequently no case series are documented in the literature. Where conservative measures fail, endoscopy/lithotripsy appear valuable next line interventions. Gallstone ileus can progress to gallstone sigmoid ileus. Abstract: Aims/Introduction: Gallstone sigmoid ileus is a rare condition that presents with symptoms of large bowel obstruction secondary to a gallstone impacted within the sigmoid colon. This arises because of three primary factors: cholelithiasis causing a cholecystoenteric fistula; a gallstone large enough to obstruct the bowel lumen; and narrowing of the bowel. We describe 3 patients treated in a district general hospital over a 3-year period, and discuss their management. Methods: Cases were retrospectively analysed from a single center between 2015 and 2017 in line with the SCARE guidelines. Results: 3 patients – 2 female, 1 male. Age: 89, 68, 69 years. 2 cholecystocolonic fistulae, 1 cholecystoenteric (small bowel) fistula. Patient 1: Unsuccessful endoscopic attempts to retrieve the (5 × 5 cm) gallstone resulted in surgery. Retrograde milking of the stone to caecum enabled removal via modified appendicectomy. Patient 2: Endoscopy and lithotripsy failed to fragment stone. Prior to laparotomy the stone was palpated in the proximal rectum enabling manual extraction. Patient 3: Laparotomy for gallstone ileus failed to identify a stone within the small bowel. Gallstone sigmoid ileus then developed. Conservative measures successfully decompressed the large bowel 6 days post-operation. Conclusions: This is the first case series highlighting the differing strategies and challenges faced by clinicians managing gallstone sigmoid ileus. Conservative measures (including manual evacuation), endoscopy, lithotripsy and surgery all play important roles in relieving large bowel obstruction. It is essential to tailor care to individual patients' needs given the complexities of this potentially life threatening condition.